2016
DOI: 10.15640/jehd.v5n1a22
|View full text |Cite
|
Sign up to set email alerts
|

Men as Early Childhood Educators: Experiences and Perspectives of Two Male Prospective Teachers

Abstract: This study explored the experiences and perspectives of two male prospective teachers pursuing studies in early childhood care and education at the national university of Trinidad and Tobago. A descriptive case study design was employed, utilizing a qualitative semi-structured interviewing technique as a data collection method for this study. Data analysis consisted of examining, categorizing, and tabulating the evidence to address the main research question of the study. Five themes emerged from the study nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
6
0
6
Order By: Relevance
“…This confirms that ECE is a feminised profession as postulated by Plan International (2013), (Vendrell et al, 2014;Breneselovic and Krnjaja, 2016;Joseph and Wright, 2016). Studies have cited cultural aspects, stereotypes, lack of social prestige and low salaries as reasons for the shortage of male teachers in preschools (Abril et al, 2008).…”
Section: Demographic Information Of Preschool Teachersmentioning
confidence: 59%
See 2 more Smart Citations
“…This confirms that ECE is a feminised profession as postulated by Plan International (2013), (Vendrell et al, 2014;Breneselovic and Krnjaja, 2016;Joseph and Wright, 2016). Studies have cited cultural aspects, stereotypes, lack of social prestige and low salaries as reasons for the shortage of male teachers in preschools (Abril et al, 2008).…”
Section: Demographic Information Of Preschool Teachersmentioning
confidence: 59%
“…Such gender stereotype continues to be accepted and sustained in domestic and cultural traditions (Trebješanin andJovanić, 2014 in Breneselovic andKrnjaja, 2016). Commenting further on the importance of using role models, as revealed by FT 7, Joseph and Wright (2016) reported that society needs to provide the boy child with role model to look up to, a strategy that can be used to attract minority group (men) into 'feminine' roles and professions, thus lead to the achievement of gender equality.…”
Section: Gender Stereotype and The Importance Of Role Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Del mismo modo, en Nueva Zelanda la realidad no es diferente, ya que menos del 1% de los docentes de la primera infancia son hombres. Esto se debe a los prejuicios públicos generalizados de que las mujeres solo pueden cumplir los roles de cuidados, sirviendo como obstáculo para los hombres al contemplar carreras en la educación temprana (Joseph y Wright, 2016). En América Latina la situación es similar.…”
Section: Maestros En La Educación Inicialunclassified
“…Historically, childcare in most homes has been seen as a woman's work, hence, the trend has spilt over to early childhood education making the female workforce to dominate. The long-standing perception from the society in those countries has been that women are more nurturing preventing men to equally participate in early childhood teaching profession [15]. Reviewing literature on early childhood teaching one finds scanty research on men as educators and in the studies that ventured into the subject mainly focus on the negative aspects of men's choice in this career.…”
Section: Men In Early Childhood Development Settingsmentioning
confidence: 99%